MicroRNAs in Alzheimer’s Disease - Wang, Mengli; Qin, Lixia; Tang, Beisha (Frontiers in Genetics, 2019)
Alzheimer’s Disease (AD) is a progressive and devastating neurodegenerative disorder. It is the leading cause of dementia in the world’s rapidly growing aging population. The characteristics of AD are memory loss and cognitive impairment, meaning patients cannot carry out their daily activities independently. The increase of AD cases poses heavy burdens on families, society and the economy. Despite frequent efforts being made to research the etiology of AD, the causes of AD remain unknown, and no curative treatments are available yet. The pathological hallmarks of AD are amyloid plaques and neurofibrillary tangles in the brain; microRNAs are endogenous 22 nucleotides non-coding RNAs that could regulate gene expression at a post-transcriptional level by transcript degradation or translation repression. microRNAs are involved in many biological processes and diseases, particularly multifactorial diseases, providing an excellent tool with which to research the mechanisms of these diseases. AD is a multifactorial disorder, and accumulating evidence shows that microRNAs play a critical role in the pathogenesis of AD. In this review, we will highlight the effect of microRNAs in different pathological processes throughout AD progression.